ANALISA PERBANDINGAN WAKTU PROYEK PERBAIKAN KAPAL KARGO MENGGUNAKAN METODE CPM DAN CCPM - Akmal Syarofi Jauhar; Fitri Hardiyanti; Yesica Novrita Devi (Proceeding Maritime Business Management Conference, 2022)
Every 5 years a cargo ship makes 2 repairs to the shipyard. As a shipyard must provide the best service in the service process and improvement results to achieve customer satisfaction. In order to achieve these goals, the basic thing that can be done is to make a plan. The method used is the Critical Path Method (CPM), using the CPM method is still not optimal because there are problems and obstacles related to human behavior. Examples of these problems are student's syndrome, multitasking and overestimated activity durations. According to these problems, namely Critical Chain Project Management (CCPM) as an alternative project scheduling solution. Based on the analysis results, the scheduling of the CCPM method produces a duration of 2 days faster than the CPM method.